Between and within breed variation in lamb survival and the risk factors associated with major causes of mortality in indigenous Horro and menz sheep in Ethiopia - Mukasa-Mugerwa, E.; Lahlou-Kassi, A.; Anindo, D.O.; Rege, J.E.O.; Tembely, S.; Tibbo, Markos; Baker, R.L. (Elsevier, 2000)
Data collected on 3256 lambs born to Horro and Menz breed ewes single-sire mated to 71 rams at the International Livestock research Institute (ILRI) Debre Berhan station between September 1992 and June 1996 were analysed for rates of survival and growth from birth to weaning. A significantly lower proportion of Menz lambs died before 1 year of age (28 percent) than the Horro lambs (59 percent). Least square means for pre- and post-weaning mortality were 8.8 and 19.3 percent respectively in Menz, and 25.3 and 34.2 percent for Horro sheeMajor causes of death were similar in Horro versus Menz lambs and were pneumonia (53 vs. 54 percent, respectively), digestive problems (14 vs. 12 percent), endoparasite infections (9 vs. 13 percent), starvation-mismothering-exposure (SME) complex (10 vs. 7 percent) and septicemia (3 vs. 2 percent). Relationships among causes of mortality with breed, birth weight (BWT), season of birth, parity, litter size and lamb health category (number of times a lamb was sick between birth and 1 year of age) were determined. The impact of these factors on mortality varied with lamb age. Lambs that were born with <2 kg BWT had a greater risk of dying from any cause except pneumonia. But even though Horro lambs were heavier than Menz at birth (2.4 vs. 2.1 kg, respectively), twice as many died before 1 year of age. The cause of mortality was further influenced by season of birth, lamb sex and health category. In addition, sires were a significant source of variation for progeny survival at 6, 9 and 12 months of age, but not at the younger ages. The best and worst Horro ram sired progeny groups that had mortality rates up to 1 year of age of 22 vs. 80 percent, respectively. The same estimates in Menz rams were 11 and 48 percent., respectively. Reduced mortality rate would significantly increase lamb output. However, isolated efforts to solve this problem are likely to have limited impact. Instead, an integrated approach to minimise the impact of underlying factors is advocated. Farm (animal) management routines that could be introduced in the short or longer term are discussed.